FROM ENVIRONMENTAL PROTECTION TO SUSTAINABLE DEVELOPMENT AND «GREEN ECONOMY»: NATIONAL PROJECT OF EDUCATION GREENING IN KAZAKHSTAN - Zhanbol O. Zhilbaev; Lyudmila V. Moiseeva (Russian State Vocational Pedagogical University, 2016)
The aim of the investigation is to show an education system role during transition to "green economy" - to a new stage of development of world economy.Methods. The methods involve the analysis and generalization of contents of the international and interstate documents of the Republic of Kazakhstan urged to provide sustainable social and economic development. Retrospective and project analysis of course processes features of social and economic system greening of Kazakhstan is also applied.Results and scientific novelty. The essence of the concepts «green economy», "ecological enlightenment", "ecological education" and "greening of society" are disclosed. The Kazakh national specifics of implementation of the international documents on implementation of model of a sustainable development are shown. The Concept of ecological formation of the Republic of Kazakhstan according to which the education system of the country is urged to create, develop and fix effectively, along with a necessary complex of knowledge, stereotypes of behavior of the people capable to make reasonable decisions is provided and to work according to legislatively consolidated nature protection regulations and standards. It is stated that greening of content of education in the republic has the developed regulatory framework, however additional measures for upgrade of an education system are necessary: its theoretical and methodological reasons, preparation and advanced training of pedagogical personnel, development of the new methodical means bring into focus an ecological orientation of training and education, etc.Practical significance. Measures for further improvement of ecological education and ecological education at all steps of education are listed.